140k views
3 votes
If f(x)=x+3 and g(x)=x-3 find (f-g)(x)

User Katelynn
by
6.0k points

1 Answer

2 votes

Answer:


(f-g)(x)
=6

Explanation:

Given:


f(x)=x+3\\g(x)=x-3

To find
(f-g)(x)

Solution:

In order to find
(f-g)(x) we will subtract the function
g(x) from
f(x)

So, we have:


(f-g)(x)
=f(x)-g(x)

Plugging in
f(x) and
g(x) in the above combinations of functions.


(f-g)(x)
=(x+3)-(x-3)

Simplifying by removing the parenthesis and reversing the signs of the terms in the parenthesis after the negative.


(f-g)(x)
=x+3-x+3

Combining like terms.


(f-g)(x)
=x-x+3+3


(f-g)(x)
=6

User Bikram
by
6.3k points